Rooted in the Soil: The Social Experiences of Black Graduate Students at a Southern Research University - Juanita Johnson-Bailey; Thomas Valentine; Ronald M. Cervero; Tuere A. Bowle (Adult Education Research Conference, 2006)
The experiences of Black graduate alumni, 1962-2003, at a major Southern Research University were examined in a comprehensive survey. The areas explored were: relationships with faculty, students, and the institution.
Keywords: Black graduate students; retention; graduate students